Comparison of Company's Financial Performance Before and During The Covid-19 Pandemic for Land and Air Transportation Service Companies in IDX - Desi Pitri Handayani (Indonesian Financial Review, 2022)
This study aims to analyze differences in the company's financial performance before and during the Covid-19 pandemic. The sample used in this study were companies in land and air transportation services listed on the Indonesia Stock Exchange for the 2018-2021 period. The number of samples used were 19 companies. While the variables used in this study include: CR, NPM, ROA, and DER. Data were collected by the documentation method. The data analysis method used descriptive statistical analysis, normality test with Kolmogorov-Smirnorv test, Paired sample t-test difference test if the data were normally distributed, and Wilcoxon Signed Rank if the data were not normally distributed. The results of this study indicate that there is no difference between CR, NPM, ROA and DER between before and during the Covid-19 pandemic.